Luaran Klinis Pasien Covid-19 Yang Menerima Remdesivir Berdasarkan Derajat Keparahan Penyakit - Andi Utari Prasetya Ningrum; Nurul Amalia Fadilah; Zulkifli; Andi Ulfah Magefirah Rasyid; Fityatun Usman; Nurfadilah; Widya Hardiyanti (Jurusan Farmasi Poltekkes kemenkes Makassar, 2026)
Coronavirus Disease 2019 (COVID-19) remains a global concern even though the international emergency status has been lifted. The resurgence of cases in several regions and the emergence of new variants indicate that this disease still has the potential to cause another wave of infections. This study aims to determine the relationship between the severity of COVID-19 and clinical outcomes in patients receiving remdesivir therapy. This study aims to determine the relationship between the severity of COVID-19 and clinical outcomes in patients receiving remdesivir therapy. This study is an observational study with a cross-sectional design using secondary data from medical records of hospitalized COVID-19 patients receiving remdesivir therapy. Clinical outcomes were determined by assessing the improvement in the patient's clinical condition, length of hospitalization, and mortality in patients. Analysis was performed using the chi-square test to examine the relationship between severity and clinical outcomes. The results showed that patients with mild and moderate severity had a higher rate of clinical improvement than severe/critical patients (100%, 94.9% vs 59.4%; p<0.001). Length of hospitalization was also shorter in mild and moderate patients compared to severe/critical, with the proportion of stays ≤14 days of 100%, 92.4%, and 69.5%, respectively (p<0.001). In addition, the mortality rate was higher in severe/critical patients at 41.6%, while in mild and moderate patients the proportion of patients who did not experience death was higher (100% and 96.6%; p<0.001). This study concluded that disease severity was closely related to the clinical outcomes of COVID-19 patients receiving remdesivir therapy, where the effectiveness of therapy was higher in patients with mild to moderate conditions.